REINTERPRETASI KEMAJUAN TEKNOLOGI MEDIS TERHADAP KETENTUAN MASA IDDAH DALAM HUKUM ISLAM - Ahmad Zaini; Burhanuddin Burhanuddin (SAMAWA, 2025)
The Iddah period is a period that must be passed by a woman whose husband has died, is divorced by her husband, or whose Iddah period has expired. The provisions of the Iddah period in Islamic law have been determined based on the evidence of the texts, which are based on the conditions of society during the time of the Prophet Muhammad SAW. However, along with the advancement of medical technology, there are several provisions of the Iddah period that need to be reviewed. This study aims to examine the provisions of the Iddah period in Islamic law in the era of advancing medical technology. This study uses a normative legal research method with an interpretation approach. The results of the study indicate that there are several provisions of the Iddah period that need to be reinterpreted in the era of advancing medical technology. For example, the provisions of the Iddah period of 4 months and 10 days for women whose husbands have died need to be adjusted to the development of medical science regarding gestational age. Reinterpretation of the provisions of the Iddah period needs to be carried out so that Islamic law remains relevant and in accordance with the times. This reinterpretation also needs to be carried out while adhering to the principles of Islamic law, namely justice, welfare, and legal certainty. Keywords: Iddah Period, Islamic Law, Advances in Medical Technology, Reinterpretation.